Wydatki na badania i rozwój podatków dochodowych wobec wyzwań strategii lizbońskiej - Pohulak-Żołędowska, Elżbieta (The research and development expenditure in income taxes vs. challenges of the lisbon strategy, 2006)
New technologies, ideas, knowledge, innovation are the „key words” of modem economy. But how to introduce innovation to enterprises? Research and development are, due to the Lisbon Strategy, probably the most important instruments meant to help the economies to develop and speed-up. The question now is: how to applicate innovation into the enlerpriccs without any additional costs? How to make the innovation to be a “wanted” good? The answer may be: the tax policy and its pro-innovative instruments, like tax allowances
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 215-221